Is it Permissible to Drill Groundwater for Business on Gili Trawangan Islands - Swahip Swahip; Ahmad Fathoni; Kusnadi Kusnadi; I Wayan Sudiyanto (Unversitas Muhammadiyah Mataram, 2026)
The pros and cons of groundwater drilling in the main tourism area of Gili Trawangan, North Lombok Regency have caused the government to revoke the groundwater extraction permits of several companies in 2022. Then there was a freshwater crisis in Gili until now in 2025. The purpose of this study was to analyze the potential of groundwater and the alleged impact of seawater intrusion in Gili as well as recommendations for groundwater business licensing policies on the island of Gili. The research method used geohydrological analysis and water balance analysis. The results showed that there are 5 (five) rock layers in Gili, namely coastal alluvial, reef, fine sand, coarse sand/reef and fine sand. Hydrogeological Borehole Log and Recovery for the aquifer layer are free or Unconfined Aquifer. In the pumping test with a capacity of 61.6 and 16.6 liters / second for 2 x 24 hours resulted in a decrease in the groundwater level of 0.5 meters and a relapse rate of only 2 minutes causing the groundwater level to return to normal height. Observations on the water quality revealed an alkaline pH and low salinity of 5 grams per liter, necessitating distillation techniques to obtain fresh water.